2011
DOI: 10.1002/em.20641
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic biomonitoring on a group of petroleum refinery workers

Abstract: Workers employed in petroleum refineries are exposed to a wide range of toxic compounds (benzene, polycyclic aromatic hydrocarbons, heavy metals, etc.) with known mutagenic and carcinogenic potential. In this study, we investigated by using the cytokinesis block micronucleus (CBMN) assay on human peripheral blood lymphocytes (PBL) whether general occupational exposure in petroleum refineries resulted in early biological effects, which would be indicative of adverse health effects in the long term. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 31 publications
1
14
0
2
Order By: Relevance
“…Indeed, recent literature suggests that there is probably no safe exposure level to benzene because it does not appear to have a functional low-dose threshold, and because the effects of exposure appear to be additive in a linear or supralinear fashion (Smith, 2010). Further, in environmental settings (as compared to work-place), exposure to compound mixtures rather than a single compound at a time is common, and simultaneous exposure to complex mixtures, including multiple carcinogens, may involve interactions and possibly synergistic effects on target organs or systems at low exposure (Basso et al, 2011). Although VOC levels were significantly elevated above concurrent local background values in the Heartland, concentrations remained below existing guidelines for short-term exposure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, recent literature suggests that there is probably no safe exposure level to benzene because it does not appear to have a functional low-dose threshold, and because the effects of exposure appear to be additive in a linear or supralinear fashion (Smith, 2010). Further, in environmental settings (as compared to work-place), exposure to compound mixtures rather than a single compound at a time is common, and simultaneous exposure to complex mixtures, including multiple carcinogens, may involve interactions and possibly synergistic effects on target organs or systems at low exposure (Basso et al, 2011). Although VOC levels were significantly elevated above concurrent local background values in the Heartland, concentrations remained below existing guidelines for short-term exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Biological evidence supports the causal linkage between certain pollutants and certain cancers, for example, between leukemia incidence/mortality and exposure to benzene (Snyder, 2002; Forrest et al, 2005) and 1,3-butadiene (Cheng et al, 2007; Kirman et al, 2010). Increased rates of leukemia, melanoma and genotoxic risk have been shown in petroleum workers and populations living downwind of petrochemical facilities such as oil refineries (Wong and Raabe, 2000; Whitworth et al, 2008; Barregard et al, 2009; Basso et al, 2011), although elevated rates and cancer mortality are not consistently observed (Tsai et al, 2004; Axelsson et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Occupational exposure limits (OELs) have been introduced by various organizations for the management of benzene exposure. As reported in [ 11 ] benzene concentrations in modern refineries in Italy have been reported to be less than 3 mg/m 3 , but investigations of petroleum refinery workers in Bulgaria found benzene concentrations levels higher than 3 mg/m 3 [ 2 ]. Exposure to benzene for petroleum refinery workers has been studied in several different countries and a significant body of exposure data is available in the scientific literature.…”
Section: Introductionmentioning
confidence: 99%
“…O estudo sugere um aumento dos riscos à saúde decorrente da emissão de benzeno no tráfego. Basso et al 89 avaliaram os efeitos da exposição a compostos tóxicos, incluindo o benzeno, em 79 trabalhadores de duas refinarias de petróleo italianas em comparação com 50 controles; os resultados encontrados mostraram um aumento significativo da formação de micronúcleos em linfócitos de sangue periférico no grupo de trabalhadores expostos.…”
Section: Normatização Da Exposição Ocupacional Ao Benzenounclassified